Comparative Study of the Shear Bond Strengths and Bracket Failure Rates of Two Orthodontic Adhesive Systems - Okeke, Azubuike Chukwubumnobi; Utomi, Ifeoma; Folaranmi, Nkiruka (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To evaluate and compare the shear bond strengths (SBS) and bracket failure rates (BFR) of orthodontic brackets bonded with Light Cure adhesive against those bonded with Self Cure adhesive. Material and Methods: The study had in vitro and in vivo parts. In the in vitro part to determine SBS of Light Bond(LB)(R) and Rely.a.Bond(RB)(R) adhesives used in bonding brackets to 88 extracted teeth, each adhesive type was used to bond 44 brackets. The clinical study was conducted to determine the BFR of the LB(R) and RB(R) adhesives by bonding 256 teeth using each adhesive type. A standardized bonding procedure was followed in both the in vitro and in vivo parts of the study. Data were analyzed using frequency, percentage, mean, independent t-test, chi-square, and Pearson Correlation statistics. A p-value of ≤ 0.05 was considered significant. SPSS version 21.0 was used to analyze the data generated. Results: There was a significantly higher mean SBS 10.6MPa for LB(R) adhesive than the 7.0MPa of the RB(R) adhesive. In the in vivo study, (LB)(R) had a greater but not significant BFR of 9.0% than RB(R) (8.0%). No significant relationship existed between the SBS of either adhesive type (as determined in vitro) and their BFR in vivo. Conclusion: Higher SBS of LB(R) did not translate to less BFR in the clinic, nor did a lower SBS of RB(R) translate to more BFR in the clinic.